Chester Terrace - Nash, John
Nash was over seventy when he sketched out proposals for the terraces of Regent's Park. Their rich stucco-plastered elevations, linked by archways and backed by a small village of service quarters, are noble in plan and grand by any standard. But the achievement is marred by clumsy detail, and the richness of the facade serves only to accentuate the sham. The real value of Nash's work in London was that it shifted the city's center to the west.